Effect of processing on the release of phenolic compounds and antioxidant activity during in vitro digestion of hulless barley - Zhuoya Xiang (Elsevier, 2021)
Hulless barley contains phenolic compounds and possesses various antioxidant activities. To clarify the effects of thermal processing and in vitro digestion on the release of phenolic compounds in hulless barley, we studied the phenolic components and antioxidant activities of hulless barley after steaming, roasting processes, and in vitro digestions. Both total phenolic content (TPC) and total flavonoid content (TFC) in raw hulless barley (HB, 4.14 mg/g DW and 1.53 mg/g DW, respectively) were higher than that of steamed hulless barley (SHB) and roasted hulless barley (RHB). In vitro digestion significantly released more ferulic acid from its bound form, but hydrolyzed some amount of flavonoid (luteolin). Chrysoeriol-7-O-glucouronide was significantly detected (412.13 µg/g DW in HB, 382.19 µg/g DW in SHB, and 396.91 µg/g DW in RHB) in all three hulless barley. The total released content of phenolic compounds obtained from each phase after digestion reached to 46% and 45% for SHB and RHB, which was higher than that in the HB (41%). The antioxidant assay (via DPPH and ABTS free radical scavenging assays) indicated that the capacity of HB was obviously higher than that of SHB and RHB in undigested group. For digested group, the ABTS+ assay order was following, undigested > oral > small intestine > gastric > large intestine. The DPPH assay results indicated the antioxidant capacity as the order of undigested > oral > gastric > large intestine. Correlation analysis showed that ferulic acid, chrysoeriol-7-O-glucouronide, luteolin, chrysoeriol, and luteolin-7-O-glucouronide contributed to the antioxidant activities. Hierarchical cluster analysis (HCA) grouped samples accordingly. Roasting process could be considered as a better daily thermal treatment for hulless barley than steaming in terms of phenolic compounds and their antioxidant activities.